Attitudes Toward Participation in Breast Cancer Randomized Clinical Trials in the African American Community: A Focus Group Study - Linden, Hannah M. (2007)
Participation of African Americans in research trials is low. Understanding the perspectives of African American patients toward participation in clinical trials is essential to understanding the disparities in participation rates compared with whites. A qualitative study was conducted to discover attitudes of the African American community regarding willingness to participate in breast cancer screening and randomized clinical trials. Six focus groups consisting of 8 to 11 African American women (N = 58), aged 30 to 65, were recruited from local churches. Focus group sessions involved a 2-hour audiotaped discussion facilitated by 2 moderators. A breast cancer randomized clinical trial involving an experimental breast cancer treatment was discussed to identify the issues related to willingness to participate in such research studies. Six themes surrounding willingness to participate in randomized clinical trials were identified: (1) Significance of the research topic to the individual and/or community; (2) level of trust in the system; (3) understanding of the elements of the trial; (4) preference for “natural treatments” or “religious intervention” over medical care; (5) cost-benefit analysis of incentives and barriers; and (6) openness to risk versus a preference for proven treatments. The majority (80%) expressed willingness or open-mindedness to the idea of participating in the hypothetical trial. Lessons learned from this study support the selection of a culturally diverse research staff and can guide the development of research protocols, recruitment efforts, and clinical procedures that are culturally sensitive and relevant.